Surgical management of hepatocellular carcinoma patients with portal vein thrombosis: The United States Safety Net and Academic Center Collaborative Analysis. Issue 2 (30th October 2020) - Ryon, Emily L.; Kronenfeld, Joshua P.; Lee, Rachel M.; Yopp, Adam; Wang, Annie; Lee, Ann Y.; Luu, Sommer; Hsu, Cary; Silberfein, Eric; Russell, Maria C.; Goel, Neha; Merchant, Nipun B.; et al.
Abstract: Background: Although consensus guidelines generally discourage any surgical management (ASM; i.e., resection and/or transplantation) in patients with hepatocellular carcinoma (HCC) and portal vein thrombosis (PVT), recent series from Asia have challenged this paradigm. Methods: Patients from the US Safety Net Collaborative database (2012–2014) with localized HCC and radiographically confirmed PVT were propensity‐score matched based on demographic and clinicopathologic factors associated with receipt of ASM and overall survival (OS). OS was compared between patients undergoing ASM and those not selected for surgery. Results: Of 1910 HCC patients, 207 (14.5%) had localized disease and PVT. The majority received either liver‐directed therapies (LDTs; 34%) and/or targeted systemic therapies (36%). Twenty‐one patients (10.1%) underwent ASM (resection [ n  = 11], transplantation [ n  = 10]); a third experienced any complication with no 30‐day mortalities. Independent predictors of undergoing ASM were younger age, recent hepatology consultation, and lower model of end‐stage liver disease (MELD) score. After matching for age, comorbidities, MELD, tumor size, receipt of LDT, or systemic therapy, OS was significantly longer for patients selected for ASM versus non‐ASM patients (median not reached vs. 5.8 months, p  < .001). Conclusion: In a large North American multi‐institutional cohort, a minority of HCC patients with PVT were selected for ASM. Resection or transplantation was associated with improved survival and may have a role in the multimodality management in selected patients.